2007
DOI: 10.1111/j.1462-2920.2007.01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of the microbial community associated with the coral Porites astreoides

Abstract: The coral holobiont is a dynamic assemblage of the coral animal, zooxanthellae, endolithic algae and fungi, Bacteria,Archaea and viruses. Zooxanthellae and some Bacteria form relatively stable and species-specific associations with corals. Other associations are less specific; coral-associated Archaea differ from those in the water column, but the same archaeal species may be found on different coral species. It has been hypothesized that the coral animal can adapt to differing ecological niches by 'switching'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
482
7
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(520 citation statements)
references
References 84 publications
26
482
7
5
Order By: Relevance
“…The diversity of microbial communities associated with corals and sponges is known to be influenced by host interactions (Wegley et al, 2007;Kimes et al, 2010;Raina et al, 2010;Fan et al, 2012), the production of antimicrobial compounds (Ritchie, 2006;Shnit-Orland and Kushmaro, 2009) and environmental conditions (Hong et al, 2009;Ceh et al, 2011). Recent studies, however, indicate that other members of the coral holobiont (in particular Symbiodinium dinoflagellates) also influence microbial community structure through release of complex carbon-containing exudates including dimethylsulfoniopropionate (DMSP; Ikeda and Miyachi, 1995;Raina et al, 2009Raina et al, , 2010.…”
mentioning
confidence: 99%
“…The diversity of microbial communities associated with corals and sponges is known to be influenced by host interactions (Wegley et al, 2007;Kimes et al, 2010;Raina et al, 2010;Fan et al, 2012), the production of antimicrobial compounds (Ritchie, 2006;Shnit-Orland and Kushmaro, 2009) and environmental conditions (Hong et al, 2009;Ceh et al, 2011). Recent studies, however, indicate that other members of the coral holobiont (in particular Symbiodinium dinoflagellates) also influence microbial community structure through release of complex carbon-containing exudates including dimethylsulfoniopropionate (DMSP; Ikeda and Miyachi, 1995;Raina et al, 2009Raina et al, , 2010.…”
mentioning
confidence: 99%
“…Active infection of Symbiodinium by members of the Phycodnaviridae was indirectly demonstrated based on the identification of phycodnavirus-like complementary DNAs in cultures of two different clades of Symbiodinium . Finally, sequence similarities to and viral-like particles reminiscent of nano-, circo-and geminiviruses, all of which are eukaryotic circular Rep-encoding ssDNA (CRESS-DNA) viruses and their associated satellites (collectively referred to 'SCSDVs' in this paper) also have been found in corals (Davy and Patten, 2007;Wegley et al, 2007;Marhaver et al, 2008;Patten et al, 2008;Vega Thurber et al, 2008;Littman et al, 2011;Rosario et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As only the WP Diseased and seawater viromes, but not the bleached and healthy viromes, contained high amounts of these viral types, it is evident that the changes detected in the relative abundance of similarities to these viral types are not the result of MDA. Finally, a previous comparative study on stressed Pacific coral species (not infected with WP) also used MDA but detected SCSDV sequences only in 2 viromes out of 6 (Vega Thurber et al, 2008), while another study on another Pacific coral species using MDA amplification identified o5% nano/ circo viruses with no similarities to satellite DNAs or geminiviruses (Wegley et al, 2007).…”
Section: Herpesviruses Dominate Healthy Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Corals harbor many essential microorganisms including viruses, bacteria, archaea, fungi, and the symbiotic algae Symbiodinium, which all play roles in maintaining the health of the coral holobiont Wegley et al 2007). …”
Section: Functional Significance Of Differing Coral-associated Bactermentioning
confidence: 99%